Whatever Happened to Human Experimentation? - Elliott, Carl (The Hastings Center report, 2016)
Several years ago, the University of Minnesota hosted a lecture by Alan Milstein, a Philadelphia attorney specializing in clinical trial litigation. Milstein, who does not mince words, insisted on calling research studies “experiments.” “Don't call it a study,” Milstein said. “Don't call it a clinical trial. Call it what it is. It's an experiment.” Milstein's comments made me wonder: when was the last time I heard an ongoing research study described as a “human experiment”? The phrase is now almost always associated with abuses. Asking a prospective subject to sign up for a medical experiment would probably get roughly the same response as asking him or her to sign up for a police interrogation. It wasn't always this way. In the early days of American bioethics, scholars used the word “experimentation” in the same neutral way that they later began to use “research study” and “clinical trial.”